(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the importance of developing English language skills among technical college students. English is a crucial tool for professional communication, academic success, and global interaction. The study highlights effective methods for teaching English in technical colleges, including interactive lessons, communicative approaches, and the integration of technology. Two key focus points are emphasized: improving students’ communicative competence and enhancing their ability to use English in professional contexts. The article also provides practical recommendations for educators to foster students’ language proficiency and confidence in real-life applications.